KINERJA ARSITEKTUR INTEROPERABILITAS E-GOVERMENT MULTI PLATFORM - Widodo, Aris Puji (MATEMATIKA, 2016)
The implementation of e-Government (e-Gov)The implementation of e-Government (e-Gov) to produce a form of relationship Government to Government (G2G). The main factor G2G about interoperability between national and local governments that have a development platform heterogeneity of e-Gov. Interoperability happens is done by creating a new architecture that has the function so that the E-Gov existing ones can communicate with each other. E-Gov Indonesia still developed separately between the central (national) and regional (province, district) or between agencies, so interoperability is happening yet fully able to walk properly. This Paper is focused on making application interoperability architecture of the E-Gov Indonesia as case studies in order to model the heterogeneous platform interoperability scheme. Architecture developed using the approach to Services Oriented Architecture (SOA) in the form of services layer to perform interoperability between heterogeneous platforms. Performance measurement is done by measuring the length of time the execution of the services contained on this architecture by using varying amounts of data.